1999
DOI: 10.1117/12.342934
|View full text |Cite
|
Sign up to set email alerts
|

<title>Finite-precision analysis of the JPEG-2000 compression standard</title>

Abstract: This study describes a detailed study of the effect of finite precision computation on wavelet-based image compression. Specifically, we examine how the quality of the final decoded image is affected by various choices that a hardware designed will have to make, such as choice of wavelet (integer or real), fixed-point attributes (number of integer and fractional bits), and compression. The algorithm studied here is that adopted by the JPEG 2000 committee, and it uses trellis-coded quantization on the wavelet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Compression and decompression errors in JPEG can result from (a) floating point errors or integer truncation errors in DCT, quantization, dequantization, and inverse DCT processes; as well as (b) errors in decompression during approximation of values input to the quantization and thresholding functions [31]. Propagation of these errors in JPEG have been analyzed elsewhere [32]. In practice, the author has observed that JPEG errors tend to be manifest as (a) obliteration of detail within a given encoding block, (b) small ringing artifacts in the decompression step, and (c) blocking effect.…”
Section: Jpeg and Jpeg-2000mentioning
confidence: 99%
“…Compression and decompression errors in JPEG can result from (a) floating point errors or integer truncation errors in DCT, quantization, dequantization, and inverse DCT processes; as well as (b) errors in decompression during approximation of values input to the quantization and thresholding functions [31]. Propagation of these errors in JPEG have been analyzed elsewhere [32]. In practice, the author has observed that JPEG errors tend to be manifest as (a) obliteration of detail within a given encoding block, (b) small ringing artifacts in the decompression step, and (c) blocking effect.…”
Section: Jpeg and Jpeg-2000mentioning
confidence: 99%